Isoflavone Intake and the Risk of Coronary Heart Disease in US Men and Women: Results From 3 Prospective Cohort Studies. Issue 14 (7th April 2020) - Ma, Le; Liu, Gang; Ding, Ming; Zong, Geng; Hu, Frank B.; Willett, Walter C.; Rimm, Eric B.; Manson, JoAnn E.; Sun, Qi
Abstract : Background: Whether soy products confer health benefits related to coronary heart disease (CHD) remains controversial because of inconsistent evidence. Methods: A total of 74 241 women from the NHS (Nurses' Health Study; 1984–2012), 94 233 women from the NHSII (Nurses' Health Study II; 1991–2013), and 42 226 men from the Health Professionals Follow-Up Study (1986–2012), who were free of cardiovascular disease and cancer at baseline, were included in the present analysis. Dietary data were updated every 2 to 4 years using a validated food frequency questionnaire. Nonfatal myocardial infarction and CHD deaths were adjudicated through reviewing medical records, death certificates, and other medical documents. Results: In these cohorts, 8359 incident CHD cases were documented during 4 826 122 person-years of follow-up. In multivariable-adjusted analyses, isoflavone intake was inversely associated with CHD (pooled hazard ratio [HR] comparing the extreme quintiles: 0.87 [95% CI, 0.81–0.94]; P =0.008). Consumption of tofu, but not soy milk, was inversely associated with the risk of CHD, with pooled HRs (95% CIs) of 0.82 (0.70–0.95; P =0.005) and 0.87 (0.69–1.10; P =0.41), respectively, comparing ≥1 serving/week with <1 serving/month. Further analyses showed that, in women, the favorable association of tofu was primarily driven by stronger inverse association of tofu intake observed in younger women before menopause and postmenopausal women without hormone use ( P interaction =0.002). Conclusions: Higher intake of isoflavones and tofu was associated with a moderately lower risk of developing CHD, and in women the favorable association of tofu were more pronounced in young women or postmenopausal women without hormone use. Abstract : Supplemental Digital Content is available in the text.